Mutual Cooperativity of Three Allosteric Sites on the Dopamine D1 Receptor - Wang, Xushan; Hembre, Erik J.; Goldsmith, Paul J.; Beck, James P.; Svensson, Kjell A.; Willard, Francis S.; Bruns, Robert F. (Molecular pharmacology, 2023)
An amine-containing molecule called Compound A has been reported by a group from Bristol-Myers Squibb to act as a positive allosteric modulator (PAM) at the dopamine D1 receptor. We synthesized the more active enantiomer of Compound A (BMS-A1) and compared it with the D1 PAMs DETQ and MLS6585, which are known to bind to intracellular loop 2 and the extracellular portion of transmembrane helix 7, respectively. Results from D1/D5 chimeras indicated that PAM activity of BMS-A1 tracked with the presence of D1 sequence in the N-terminal/extracellular region of the D1 receptor, a unique location compared with either of the other PAMs. In pairwise combinations, BMS-A1 potentiated the small allo-agonist activity of each of the other PAMs, while the triple PAM combination (in the absence of dopamine) produced a cAMP response about 64% of the maximum produced by dopamine. Each of the pairwise PAM combinations produced a much larger leftward shift of the dopamine EC50 than either single PAM alone. All three PAMs in combination produced a 1000-fold leftward shift of the dopamine curve. These results demonstrate the presence of three non-overlapping allosteric sites that cooperatively stabilize the same activated state of the human D1 receptor. Deficiencies in dopamine D1 receptor activation are seen in Parkinson disease and other neuropsychiatric disorders. In this study, three positive allosteric modulators of the dopamine D1 receptor were found to bind to distinct and separate sites, interacting synergistically with each other and dopamine, with the triple combination causing a 1000-fold leftward shift of the response to dopamine. These results showcase multiple opportunities to modulate D1 tone and highlight new pharmacological approaches for allosteric modulation of G-protein–coupled receptors.